MAC-Layer QoS Management for Streaming Rate-Adaptive VBR Video over IEEE 802.11e HCCA WLANs - Jianfei Cai; Deyun Gao; Jianhua Wu (Advances in Multimedia)
With the increasing popularity of using WLANs for Internet access, the HCCA mechanism in IEEE 802.11e WLANs has received much more attention due to its efficiency in handling time-bounded multimedia traffic. To achieve high network utilization and good end-to-end QoS in the scenario of VBR video over HCCA is a very challenging task because of the dynamics coming from both the network conditions and the video content. In this paper, we propose a cross-layer framework for efficiently delivering multiclass rate-adaptive VBR video over HCCA. The proposed framework consists of three major modules: the MAC-layer admission control, the MAC-layer resource allocation, and the application-layer video adaptation. Experimental results demonstrate the effectiveness of each individual module and the advantage of dynamic interactions among different modules.